The Augustan Principate: its lights and its shadows in USA (1776-1860) - Martínez Maza, Clelia (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2017)
It is clear the ongoing importance of the classics before the Civil War in the United States and their formative influence upon the Founders. The literature of the Augustan Principate provided one of their principal sets of ideological tools: an agricultural lifestyle, a lifestyle deified by Augustan poets, a society of Virgilian farmers and a democratic republic supported by free landholders. However, Augustus became a code word for tyrant. The Founding Fathers perceived him as an antimodel and he was rejected as a political canon because of the unlimited power and lifetime term of the Roman Emperors.